SnRK2 Protein Kinases and mRNA Decapping Machinery Control Root Development and Response to Salt. Issue 1 (30th September 2019) - Kawa, Dorota; Meyer, A. Jessica; Dekker, Henk L.; Abd-El-Haliem, Ahmed M.; Gevaert, Kris; Van De Slijke, Eveline; Maszkowska, Justyna; Bucholc, Maria; Dobrowolska, Grażyna; De Jaeger, Geert; Schuurink, Robert C.; Haring, Michel A.; et al.
Abstract : Salinity stress shapes root development through control of mRNA stability and requires the partially redundant function of SnRK2 protein kinases to modulate transcript levels. Abstract: SNF1-RELATED PROTEIN KINASES 2 (SnRK2) are important components of early osmotic and salt stress signaling pathways in plants. The Arabidopsis ( Arabidopsis thaliana ) SnRK2 family comprises the abscisic acid (ABA)–activated protein kinases SnRK2.2, SnRK2.3, SnRK2.6, SnRK2.7, and SnRK2.8, and the ABA-independent subclass 1 protein kinases SnRK2.1, SnRK2.4, SnRK2.5, SnRK2.9, and SnRK2.10. ABA-independent SnRK2s act at the posttranscriptional level via phosphorylation of VARICOSE (VCS), a member of the mRNA decapping complex, that catalyzes the first step of 5′mRNA decay. Here, we identified VCS and VARICOSE RELATED (VCR) as interactors and phosphorylation targets of SnRK2.5, SnRK2.6, and SnRK2.10. All three protein kinases phosphorylated Ser-645 and Ser-1156 of VCS, whereas SnRK2.6 and SnRK2.10 also phosphorylated VCS Ser-692 and Ser-680 of VCR. We showed that subclass 1 SnRK2s, VCS, and 5′ EXORIBONUCLEASE 4 (XRN4) are involved in regulating root growth under control conditions as well as modulating root system architecture in response to salt stress. Our results suggest interesting patterns of redundancy within subclass 1 SnRK2 protein kinases, with SnRK2.1, SnRK2.5, and SnRK2.9 controlling root growth under nonstress conditions and SnRK2.4 and SnRK2.10 acting mostly in response to salinity. We propose that subclass 1 SnRK2s function in root development under salt stress by affecting the transcript levels of aquaporins, as well as CYP79B2, an enzyme involved in auxin biosynthesis.